2017
DOI: 10.1038/s41467-017-01043-z
|View full text |Cite
|
Sign up to set email alerts
|

A parsimonious neutral model suggests Neanderthal replacement was determined by migration and random species drift

Abstract: Most hypotheses in the heated debate about the Neanderthals’ replacement by modern humans highlight the role of environmental pressures or attribute the Neanderthals’ demise to competition with modern humans, who occupied the same ecological niche. The latter assume that modern humans benefited from some selective advantage over Neanderthals, which led to the their extinction. Here we show that a scenario of migration and selectively neutral species drift predicts the Neanderthals’ replacement. Our model offer… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 79 publications
1
31
0
Order By: Relevance
“…One difference may be that leaky replacement implies that introgressed alleles increase the fitness of the invading species (as in adaptive introgression: Hedrick, ; Pardo‐Diaz et al, ; Racimo, Sankararaman, Nielsen, & Huerta‐Sánchez, ), but the consulted literature is not explicit at this point. In spite of a long history of investigation, considerable debate revolves around whether Neanderthals became extinct because of climate change or competition with anatomically modern humans (Banks et al, ; Benito et al, ; Gilpin, Feldman, & Aoki, ; Kolodny & Feldman, ; Melchionna et al, ) and the degree to which they hybridized (Currat & Excoffier, ; Neves & Serva, ; Villanea & Schraiber, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One difference may be that leaky replacement implies that introgressed alleles increase the fitness of the invading species (as in adaptive introgression: Hedrick, ; Pardo‐Diaz et al, ; Racimo, Sankararaman, Nielsen, & Huerta‐Sánchez, ), but the consulted literature is not explicit at this point. In spite of a long history of investigation, considerable debate revolves around whether Neanderthals became extinct because of climate change or competition with anatomically modern humans (Banks et al, ; Benito et al, ; Gilpin, Feldman, & Aoki, ; Kolodny & Feldman, ; Melchionna et al, ) and the degree to which they hybridized (Currat & Excoffier, ; Neves & Serva, ; Villanea & Schraiber, ).…”
Section: Discussionmentioning
confidence: 99%
“…The inferred species transition that was labelled as "leaky replacement" (Pääbo, 2015; see also Gibbons, 2011), parallels that of a moving hybrid zone leaving a genetic footprint. One difference may be that leaky replacement implies that introgressed alleles increase the fitness of the invading (Banks et al, 2008;Benito et al, 2017;Gilpin, Feldman, & Aoki, 2016;Kolodny & Feldman, 2017;Melchionna et al, 2018) and the degree to which they hybridized (Currat & Excoffier, 2004;Neves & Serva, 2012;Villanea & Schraiber, 2019).…”
Section: Genetic Footprints and Parallels With The Demise Of Homo mentioning
confidence: 99%
“…With climate change now central in the scientific discourse, many recent studies suggest that climate played an important role in the environmental changes making AMH more competitive than other Homo species, or allowing opening ecological corridors for dispersal of Homo sapiens out of Africa [3442]. An opposite view is that AMH and Neanderthals actually had no competitive advantage over each other [43]. The argument, based on a numerical model, is that, because AMH’s population was much larger than that of Neanderthals [4446,12], AMH’s were statistically more likely to reach fixation in both Africa and Europe.…”
Section: Introductionmentioning
confidence: 99%
“…This replacement has been extensively studied and debated (e.g. [28][29][30][31][32][33][34][35][36][37]). Less attention, however, has been given to the fact that contact in the Levant was made much earlier than the initiation of the replacement phase [11].…”
Section: Introductionmentioning
confidence: 99%
“…Once the interaction front was destabilized, presumably around 45-50kya, other processes, previously overshadowed by disease burden, would then have been responsible for the replacement of Neanderthals by Moderns [34,36,37,58], although it has been suggested that disease transmission dynamics could also have played a prominent role in the replacement process [53,59,60]. Our model supports this possibility: because conditions relating to disease dynamics need not have been symmetric between Moderns and Neanderthals -for example, the Moderns' tropical pathogen package may have been more burdensome to the Neanderthals than the Neanderthals' temperate pathogen package was to Moderns, following the pattern of decreasing pathogen burden with latitude [61,62] -the Moderns may have overcome the disease burden from contact sooner than Neanderthals.…”
Section: Introductionmentioning
confidence: 99%